Organic Farming: Is a Metamorphosis of Modern Agricultural Imperialism or a Postmodern Agricultural Model? - Yana, Hamyana; Hidayat, Kliwon; Sukesi, Keppi; Yuliati, Yayuk (Anuário do Instituto de Geociências, 2022)
The implementation of organic farming programs in Indonesia involves various actors and various interests in it. The relationship between actors and their interests has positioned organic agriculture at the intersection between modern agricultural camouflage and the antithesis of modern agriculture (postmodern agriculture). How did this happen? so this research is very important to provide a complete picture in describing the involvement of actors and power relations as one of the key factors that will determine the formulation of policies for developing organic agriculture in the future. This research used a qualitative method with a case study approach. Data collection techniques were carried out by in-depth interviews, observations, and document studies. The research data were analyzed concerning the Miles and Huberman (2002) framework, which consisted of stages of data reduction, analysis formulation, and concluding. The results showed that there were four typologies of actors, namely, type A actors oriented to spiritual values; actor type B oriented to moral values; type C actor is oriented to rational values and type D actor is oriented to political/power values. The struggle between actors is dominated by driving actors (advanced farmers or champions, state apparatus, capitalists) who have stronger knowledge power. The rhetoric and images narrated by the driving actors then become tools for domination to seize the rights of other actors with the interests and powers attached to each actor. The implementation of organic agriculture which is full of power interests puts organic farming programs in Indonesia trapped in a market trap and a poor meaning reduction of moral values, human values, spiritual values, and ecological values.